COSTABILITY OF IMPLEMENTING STEAM EDUCATION IN MODERN EDUCATION - Berdieva Gulnoza Rizokulovna (European International Journal of Pedagogics, 2024)
In this article, the many advantages and relevance of STEAM education in today's modern education system are discussed.